An investigation of oblique incidence propagation of radio pulses between Grahamstown and Durban - Nadasen, Arunajallam (Rhodes University, Faculty of Science, Department of Physics, 1968)
This thesis describes the investigation carried out on the propagation of radio pulses of frequency 4.73 Mc/s between Grahamstown and Durban. The thesis is divided into two sections - A and B. Section A consists of two chapters. The introductory chapter gives a brief account of how the existence of the ionosphere came to be known. Then follows a description of the different layers of ionization and a review of the theories that have been propounded on the formation of these layers. Chapter 2 deals with the apparatus which includes the transmitter in Grahamstown and the receiving apparatus in Durban. The receiving apparatus comprises: i) a superheterodyne receiver whose gain was high (between 130 and 140 dbs); (ii) a time delay calibrator which could measure time differences of 100 Î¼sec fairly accurately; (iii) a 310 A Tektronix oscilloscope; (iv) a continuously running 35 mm recording camera. Section B is made up of three chapters and is concerned with the actual analysis of the data recorded. The theory of propagation of radio waves in the ionosphere is discussed in Chapter 3. The effects of the magnetic field are neglected since it is found that the error introduced would not make the results unacceptable. Chapter 4 contains the analysis of the data recorded. One summer day and one winter day are discussed in detail in order to obtain the pattern of the diurnal variations for both summer and winter. Some interesting phenomena are also dealt with. An attempt to do ray tracing was successful and the paths followed by a Pedersen and a lower ray from Grahamstown to Durban have been drawn. New topics for further research are discussed in Chapter 5. There are two appendices. Appendix I gives the time delays of all the pulses recorded and their possible identifications. An overall picture of the propagation via the various layers throughout the day (both for summer and for winter is presented in Appendix II.
Keywords: Ionospheric radio wave propagation; Radio waves